Розробка бізнес-моделі цифрової трансформації в Україні: виклики, можливості та стратегічні орієнтири - Шостак, Людмила Василівна; Shostak, L. V.; Більо, І. О.; Bilo, I. O. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті здійснено комплексний аналіз процесу розробки бізнес-моделі цифрової трансформації в контексті економічного та соціального середовища України. Розглянуто ключові виклики, які супроводжують впровадження цифрових технологій у вітчизняних підприємствах, зокрема технічні, організаційні та інституційні бар’єри. Окрему увагу приділено вивченню можливостей, які відкриваються завдяки цифровізації, включаючи підвищення операційної ефективності, розвиток нових продуктів і послуг, а також покращення взаємодії з клієнтами. Запропоновано стратегічні орієнтири, що базуються на системному підході до формування бізнес моделі, спрямовані на забезпечення гнучкості, інноваційності та адаптивності до мінливих ринкових умов. Викладені рекомендації з управління цифровими змінами, які дозволяють підприємствам України забезпечити сталий розвиток та підвищити конкурентоспроможність у глобальному економічному просторі. /// EN: The development of digital transformation business models in Ukraine has become a pivotal element of economic modernization, particularly under the conditions of global instability and military conflict. This article explores the current challenges, opportunities, and strategic priorities for implementing digital business models, offering a structured approach to transition amid turbulent socio-economic conditions. The research highlights that the digital transformation of Ukrainian enterprises is driven by several factors: globalization of markets, the need to reduce operational costs, increased demand for personalized services, and integration into the European digital space. The war in Ukraine has significantly accelerated digitalization, compelling businesses to adopt innovative technological solutions to maintain operations, ensure resilience, and access international markets. The study presents a SWOT analysis of digital transformation processes, identifies core weaknesses such as insufficient infrastructure, limited digital competencies, and cybersecurity risks, while also emphasizing opportunities, including access to EU grant programs, international technological partnerships, and state-backed digital initiatives. A step-by-step scheme of strategic transition to digital business models is proposed, emphasizing investment in human capital, digital innovation ecosystems, and regulatory support. Moreover, strategic orientations are defined, such as the development of a national digitalization strategy, digital sovereignty, and cyber resilience, which are vital for the reconstruction and sustainable development of Ukraine's economy in the post-war period. The paper concludes that a comprehensive, integrated approach to digital transformation can become a cornerstone of Ukraine’s economic recovery and long-term competitiveness. Digital tools not only facilitate adaptation and business continuity but also offer mechanisms for rapid integration into global value chains. The transformation of business models under conditions of uncertainty requires coordinated action between the state, private sector, and civil society to create a resilient, innovation-driven economy.
Development of a business model for digital transformation in Ukraine: challenges, opportunities, and strategic guidelines
Keywords: цифрова трансформація; бізнес-модель; цифрова економіка; стратегічне управління; інновації; Україна; конкурентоспроможність; технологічні виклики; digital transformation; business models; Ukraine; strategic development; digital economy; cyber resilience; innovation; globalization; post-war recovery; digitalization